Changes in the Ripening Stage and Quality of Her (Ziziphus mauritiana L.) cv. Mundia After Exogenous Application of Ethephon - Gupta, N K; Gupta, Sunita; Goyal, S K; Sharma, B M (Annals of Arid Zone, 2016)
Short Communication